2017
DOI: 10.1097/pcc.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

A Population Pharmacokinetic Analysis to Study the Effect of Therapeutic Hypothermia on Vancomycin Disposition in Children Resuscitated From Cardiac Arrest*

Abstract: Objective Limited data exist on the effects of therapeutic hypothermia (TH) on renal function and pharmacokinetics in pediatric patients after cardiac arrest (CA). The objective was to describe the differences in vancomycin disposition in pediatric patients following CA treated with either TH or normothermia (NT) using population pharmacokinetic modeling. Design Single-center, retrospective cohort study Setting A tertiary care hospital pediatric and cardiac intensive care unit Patients Fifty-two pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 29 publications
0
39
0
4
Order By: Relevance
“…A logic next step seems to incorporate both age-and disease related co-variates in dosing guidelines using modelling and simulation. Most of the PopPK modelling studies in this review have incorporated (allometrically scaled) age and/or weight covariates in their final models [21,25,26,28,51,52,55,57,61,65]. However, models incorporating (bio) markers of organ failure (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A logic next step seems to incorporate both age-and disease related co-variates in dosing guidelines using modelling and simulation. Most of the PopPK modelling studies in this review have incorporated (allometrically scaled) age and/or weight covariates in their final models [21,25,26,28,51,52,55,57,61,65]. However, models incorporating (bio) markers of organ failure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…eGFR, serum creatinin, albumin, C-reactive protein, transaminases) as covariate were limited [21,25,26,28,51,52,55,57]. Of the 48 studies, only 5 PK models have incorporated eGFR in their estimations for drug Cl [21,26,51,55,57] and only 3 additional studies found a significant relation between serum creatinine and drug concentration [29,45,60]. Other studies have either not investigated this relationship or found the addition of creatinine clearance to be non-significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Known effects of hypothermia include urinary diuresis, renal tubular dysfunction, reduced creatinine clearance and increased excretion of electrolytes which result in depletion of important elements [17,31,[48][49][50][51]. Zane et al recently published data on the differences in vancomycin disposition in pediatric patients following cardiac arrest treated with either TH or normothermia [52]. They noted that children receiving hypothermia and/or with decreased renal function had lower vancomycin clearances based on a retrospectively fitted twocompartment model in children who experience cardiac arrest.…”
Section: Renal Effectsmentioning
confidence: 99%